2011
DOI: 10.1039/c0cp02880k
|View full text |Cite
|
Sign up to set email alerts
|

Electronically excited states of membrane fluorescent probe 4-dimethylaminochalcone. Results of quantum chemical calculations

Abstract: Quantum-chemical calculations of ground and excited states for membrane fluorescent probe 4-dimethylaminochalcone (DMAC) in vacuum were performed. Optimized geometries and dipole moments for lowest-lying singlet and triplet states were obtained. The nature of these electronic transitions and the relaxation path in the excited states were determined; changes in geometry and charge distribution were assessed. It was shown that in vacuum the lowest existed level is of (n, π*) nature, and the closest to it is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Previous quantum chemical calculation by Romanov et al has shown that after photoexcitation 4-dimethylaminochalcone undergoes efficient 1 (π, π)* → 1 (n, π)* → 3 (π, π)* relaxation process in nonpolar media. With the increase in solvent polarity, the charge transfer state is quickly stabilized to ICT′ (solvent-stabilized ICT state) state by dipolar interaction with solvent molecules, which will suppress the efficient ISC process …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous quantum chemical calculation by Romanov et al has shown that after photoexcitation 4-dimethylaminochalcone undergoes efficient 1 (π, π)* → 1 (n, π)* → 3 (π, π)* relaxation process in nonpolar media. With the increase in solvent polarity, the charge transfer state is quickly stabilized to ICT′ (solvent-stabilized ICT state) state by dipolar interaction with solvent molecules, which will suppress the efficient ISC process …”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies have shown that DEAHC has no or weak green fluorescence in solution but is strongly emissive around 700 nm when in bulk crystals; DEAMC is dark in both crystalline form and nonpolar solution but emits brightly in polar solution. , To explore their crucial microscopic dynamic mechanism, in this work, solvent-dependent excited state dynamics of both DEAMC and DEAHC are extensively investigated by using steady state spectroscopy, femtosecond and nanosecond transient absorption spectroscopy. We found that dramatic solvation effect induces stabilization of ICT state, restricting efficient formation of triplet states, enhancing the fluorescence yield of DEAMC . ,, Moreover, the stronger solvation process in polar solvents can further facilitate efficient ESIPT reaction in DEAHC .…”
Section: Introductionmentioning
confidence: 85%
“…The largest shift (0.8 eV) corresponds to the 4-(N, N dimethylamino ′ − )-chalcone, which is shown to have also high fluorescence quantum yield (0.6 in dimethylformamide) when compared to the non-fluorescent chalcone [12,14]. In paper [8] the energies of singlet and triplet ππ ⁎ and nπ ⁎ excited states were simulated using quantum chemical approach for 4-(N, N dimethylamino ′ − )-chalcone and its complex with water molecules in a gas phase. However, dipoledipole interactions were not taken into account, so the obtained results can be compared only to spectral properties in binary mixture of nonpolar solvent with small amount of water.…”
Section: Introductionmentioning
confidence: 99%
“…However, it hardly be said about the properties of chalcone and its amino-derivatives. Due to the flexible -CQC-C(-)QO chain and non-planar structure [8,9] they have distinguishing features, such as fluorescence quenching in protic solvents [4,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, chalcones are well known for biological activities such as anti-inammatory, 14 antibacterial 15,16 anti-parasitic, 17 antitumor 18 and antifungal. 19,20 This is due to a, b unsaturated keto group (-C]C-C(-)]O) and nonplanar structure 21,22 present in chalcones. A compound having donor-acceptor functionality with conjugation called a pull-push system, displays interesting photophysical properties.…”
Section: Introductionmentioning
confidence: 99%